Technology acceptance model (TAM) and social media usage: an empirical study on Facebook. Issue 1 (2014) - ,; ,; ,; ,
Abstract : Purpose – Given the widespread popularity of social media, such as Twitter, Facebook, Google+, and LinkedIn, theorizing and understanding the user attitude and usage behavior of social media site is fundamental in developing future understandings and deployment of these new technologies. One approach to such studies on drivers of social media usage behavior would be to revisit the technology acceptance model (TAM). The purpose of this paper is to discuss these issues.Design/methodology/approach – Decades of extensive research have focussed on validating the TAM, proposed by Davis (1986), for various types of information systems and communication technologies. TAM forecasts individual adoption and voluntary use of technology. This study examines individual adoption behavior of the most popular social networking site Facebook. The influences on the intention of using social networking based on individual's perceived ease of use (EU), the user's critical mass (CM), social networking site capability (CP), perceived playfulness (PP), trustworthiness (TW), and perceived usefulness (PU) is empirically examined with a primary data set of 398 users of Facebook gathered from a web‐based questionnaire survey.Findings – The results demonstrate that the revised social media TAM model proposed in this study supports all the hypotheses of social media usage behavior. The results of this study provide evidence for the importance of additional key variables to TAM in considering user engagement on social media sites and other social‐media‐related business strategies.Originality/value – Based on our review of existing scientific literature on social media, few empirical studies have been conducted to scientifically evaluate and explain the usage behavior of social media using Facebook. A validated instrument of usage behavior of social media can provide usability experts and practitioners with a validated tool to assess social media acceptance and usage behavior. This can help us gain a better understanding of "who is and who is not using these sites, why and for what purposes" (Boyd and Ellison, 2007).